2020
DOI: 10.1080/09540105.2020.1786669
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of animal plasma protein supplementation in mice undergoing simultaneous gut and lung inflammation

Abstract: We aimed to determine whether dietary supplementation with spray-dried porcine plasma (SDP) is effective in mice exposed to a dual S. aureus enterotoxin B (SEB) and lipopolysaccharide (LPS) challenges inducing simultaneous inflammation in the gut and lung. Male C57BL/6 mice were fed control or SDP-supplemented diets from weaning for 14 days. At the end of the experimental period, animals received LPS intranasal followed by SEB intraperitoneal doses. The dual challenge increased leukocyte recruitment into mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…Challenging mice and rats with SEB via intraperitoneal injection resulted in a strong intestinal inflammation as indicated by leukocyte infiltration, the release of inflammatory mediators, and increase permeability of the intestinal mucosa. SDP and IgG were shown to attenuate these changes by reducing the activated immune cells, pro-inflammatory cytokines, and intestinal barrier permeability [32,36,39,46]. In contrast to the modulated immune responses in the rodent models of inflammation, the current study found that SDP increased circulatory immune responses in shrimp.…”
Section: Plos Onecontrasting
confidence: 64%
See 1 more Smart Citation
“…Challenging mice and rats with SEB via intraperitoneal injection resulted in a strong intestinal inflammation as indicated by leukocyte infiltration, the release of inflammatory mediators, and increase permeability of the intestinal mucosa. SDP and IgG were shown to attenuate these changes by reducing the activated immune cells, pro-inflammatory cytokines, and intestinal barrier permeability [32,36,39,46]. In contrast to the modulated immune responses in the rodent models of inflammation, the current study found that SDP increased circulatory immune responses in shrimp.…”
Section: Plos Onecontrasting
confidence: 64%
“…However, it is widely accepted that health-promoting effect of SDP is mainly attributed to the immunomodulatory property of SDP on the intestinal barrier [3,6,31]. The anti-inflammatory activities of SDP including suppressing pro-inflammatory cytokine production (e.g., TNF-α and IFN-γ), stimulating anti-inflammatory cytokine production (e.g., IL-10 and TGF-β), inhibiting inflammatory cell infiltration in the gut mucosa and lamina propria, and improving intestinal barrier function are well-recognized especially in rodent models [32][33][34][35][36][37], and in weaned pigs to a lesser extent [8,38]. Continuous exposure of the intestinal mucosa to bacterial pathogens or toxins can cause chronic overstimulation of the mucosal immune system, thereby impairing intestinal barrier function and resulting in poor nutrient absorption.…”
Section: Discussionmentioning
confidence: 99%
“…A dietary supplement containing over 90% bovine serum protein (>50% immunoglobulins) reduces inflammatory markers and tissue damage in mice models of colitis [ 10 , 11 , 12 ] and mucositis [ 13 ]. Simultaneous protection against lung and colon inflammation has been documented for porcine SDP [ 14 ]. Further, the latter has been recently shown to exert neuroprotective activity in a senescence murine model [ 15 ] and partial protection against intraperitoneal LPS challenge in pregnant mice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%